Expressão transcricional de ERFs em arroz submetidos ao estresse por ferro - Kruger, Mariana Madruga (2013)
Rice (Oryza sativa L.) is a crop of high nourishment and financial importance, largely grown in flat and flooded ecosystems which present deficient drainage conditions. Under such conditions, the low redox potential of the environment leads to the reduction of iron present in the soil solution, which becomes readily available and can become toxic to the plant when absorbed in excess. Iron toxicity is one of the most important types of abiotic stress, limiting the production of irrigated rice worldwide. In rice growth areas of Rio Grande do Sul, Brazil, iron has caused toxicity problems and the use of tolerant cultivars becomes an important strategy in solving the problem, where the identification of genes is necessary in face of the different mechanisms which confer this tolerance to the plants for application in improvement programs. Recent studies discovered the importance of some transcription factors responsive to ethylene (ERFs) in vegetable response to different kinds of stress. Thus, the aim of this study was to evaluate the differential expression profile of 32 ERFs in rice subjected to iron stress conditions in three cultivars; Nipponbare, Epagri 108 (tolerant to iron toxicity) and Br-Irga 409 (sensitive to iron toxicity) and to identify cis elements in the ERF gene promotion region in rice. The results obtained demonstrate that in rice, most members of the ERF family showed differential profiles in the cultivars Npponbare, Epagri 108 and Br-Irga 409, under iron stress conditions. ERFs expressed in the tolerant cultivar (Epagri 108) may be potentially important in the induction of tolerance while those which were more highly induced in the sensitive cultivar (Br-IRGA 409) belong to a response mechanism which is not efficient. Analyses of cis elements demonstrate that the regulation of expression of all analyzed ERFs takes place in complex form and that there exists an association between the presence of a specific cis element and the expression profile.